1996
DOI: 10.1002/(sici)1097-0320(19960601)24:2<181::aid-cyto11>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence analysis of carrier rat and human erythrocytes loaded with FITC-dextran

Abstract: Rat and human erythrocytes are inherently different with respect to slow dialysis encapsulation used in preparing carrier erythrocytes. The incorporation process, commonly measured with radioactive tracers, is always larger in human erythrocytes, mainly because the rat carrier cells are more fragile. When FITC‐Dextran (Dx) is used in the encapsulation process, and loaded rat and human RBCs are studied by fluorescence intensity, some additional events are evident. Not all cells of each population appear with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…RMSN-PEG-10 exhibit successful incorporation into the RBCs compared to the larger sizes of particles (25, 50, and 200 nm), which indicated that RBC membrane pores allow a preferential embedding of nanoparticles with smaller sizes (Figure ). Actually RMSN-PEG-10 suspended in HEPES buffer have a Z -average = 26.4 ± 0.75 nm due to hydration and some slight aggregation , (Table S2), which meant that the selection of the particle sizes of RMSN for encapsulation in RBCs by hypotonic treatment requires a hydrodynamic diameter below about 30 nm. To verify the structural integrity of the engineered RMSN-RBCs, the interior of the cells was examined via confocal and scanning electron microscopy (SEM) imaging.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RMSN-PEG-10 exhibit successful incorporation into the RBCs compared to the larger sizes of particles (25, 50, and 200 nm), which indicated that RBC membrane pores allow a preferential embedding of nanoparticles with smaller sizes (Figure ). Actually RMSN-PEG-10 suspended in HEPES buffer have a Z -average = 26.4 ± 0.75 nm due to hydration and some slight aggregation , (Table S2), which meant that the selection of the particle sizes of RMSN for encapsulation in RBCs by hypotonic treatment requires a hydrodynamic diameter below about 30 nm. To verify the structural integrity of the engineered RMSN-RBCs, the interior of the cells was examined via confocal and scanning electron microscopy (SEM) imaging.…”
Section: Results and Discussionmentioning
confidence: 99%
“…4,5,11,12 Hypotonic dialysis is based on the exposure of RBCs to the substance to be encapsulated contained in a dialysis bag to the hypotonic buffer, so that nanoparticles can enter RBCs, and the pores were resealed in an isotonic buffer. 24,25 To confirm the integrity of the hypotonic dialysis method in this study, FITC−dextran acts as a positive control 26 which shows the emission of green fluorescence on the RBCs (denoted as dextran@RBCs) in Figure S4. RMSN-PEG-10 exhibit successful incorporation into the RBCs compared to the larger sizes of particles (25, 50, and 200 nm), which indicated that RBC membrane pores allow a preferential embedding of nanoparticles with smaller sizes (Figure 3).…”
Section: Hemolytic Activity Of Msnsmentioning
confidence: 99%
“…Additional fluorescent markers were used in N. coccinea and Drosera capensis in order to confirm the results gained by FITC‐BSA: FITC‐Dextran has been shown to label endocytotic compartments in animal (Lencer et al. , 1990; Alvarez et al. , 1996) and plant cells (Cole et al.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The various benefits of RBC carriers (e.g., biocompatibility, biodegradability, protection of drug from body, protection of body from drug) has resulted in a significant body of research on RBC-based drug delivery. 17,18,19 Compared with drug delivery applications, little research has been performed on loading fluorescent materials into RBCs. FITC-dextran was loaded into RBCs by Alvarez et al and Scott et al; a broad distribution of fluorescence intensities was revealed upon analysis by cell sorting methods.…”
Section: Functionalized or Loaded Red Blood Cellsmentioning
confidence: 99%